Asphalt modified by thermoplastic elastomer based on recycled rubber. (15th September 2015) - Wang, Shifeng; Wang, Qiang; Wu, Xiaoyu; Zhang, Yong
Highlights: Asphalt modified by TPE based on recycled rubber has been discussed. Dynamic devulcanization and dynamic vulcanization improve the dispersion of GTR in the asphalt. Asphalt modified by TPE has good processing property and high storage stability. Abstract: Thermoplastic elastomers (TPEs) based on ground tire rubbers (GTRs) and polyethylene were used for asphalt modification. TPEs were prepared by dynamic devulcanization (DD) in the presence of desulfurizer and dynamic vulcanization (DV) with sulfur, respectively. Structure and properties of TPEs and their modified asphalts were characterized by morphology, thermal, sol–gel content and mechanical testing. It was found that DD process decreased the physical properties, while the DV process strengthened that of TPE. The results also showed that the compatibility between PE and GTR was improved by DV, which further enhanced physical property and stabilized the TPE in the asphalt.